The singular set of ω-minima - Kristensen, J; Mingione, G (2005)
We consider Ω-minima u: ω ⊃ ℝ → ℝ Nof convex variational integrals in the vectorial case n≧2, and we provide estimates for the Hausdorff dimension of their singular sets. © Springer-Verlag (2005).